PENERAPAN PENDEKATAN KETERAMPILAN PROSES UNTUK MENINGKATKAN HASIL BELAJAR SISWA PADA MATERI ENERGI BUNYI - Cacik, Sri; Rinayanti, Ulfa (Universitas Nahdatul Ulama Surabaya, 2017)
Based on observation conducted at SDN Ngadirejo II Rengel Tuban, the researcher found that the learning process is still less effective. The students had difficulty in understanding the science material about the energy of sound. It is caused by several factors, one of which is the informtion transfer just use the direct instruction method, the Students opportunity to develop the skills to ask and submit answers are still lacking, so that student learning outcomes under KKM. Therefore, the researcher applied the science process skills approach to improving classroom student learning outcomes. This research used the Classroom Action Research (CAR) as its design, which is each cycle consists of four phases: planning, implementation, observation, and reflection. the research Subjects were students in the fourth grade in SDN II Ngadirejo Rengel Tuban, which has 21 students. Data collecting technique is done through tests of learning outcomes with achievement test sheet instruments. The indicators of the successfullness of the study are measured through the percentage of individual completeness and classroom. The results showed that the students' learning outcomes increased with the percentage of classical completeness by 42,85% in prestudy to 66,67% in the first cycle and 95,23% in the second cycle. The obstacle encountered in the study was that the teachers and students at SDN Ngadirejo II Rengel Tuban were not used to apply the science process skills approach.